ICT intervention and palliative care: a review - Mohamadali, Noor Azizah; Adebiyi, Lookman (2015)
Palliative Care (PC) has been introduced in Malaysia for more than two decades now. Research on Palliative Care is becomes crucial as ageing population is increasing from year to year. To address this, research on the use of ICT intervention in PC also expanding whereby variety of ICT tools are introduced and being used in order to increase accessibility to healthcare sector services. For a patient to have a better quality of end-of-life, ICT intervention is vital. Despite the fact that ICT intervention could improve the quality of life of patients, access to technology is still insufficient in many developing countries around the world. A review of ICT intervention on PC is important for addressing the limitation of ICT Intervention in developing countries including Malaysia. This paper argues that developing countries are still far from embracing into ICT. Moreover, it remains a big challenge for many developing countries when its existence is yet to be fully understood and supported by the public as well as by the key decision makers. This review shows that the gap of ICT intervention between developed countries and developing countries are still huge and this needs to be addressed accordingly. Further research is needed to investigate the role of ICT in palliative care and how ICT intervention could improve quality of care for patients. Nevertheless, it is equally important to measure level of acceptance of ICT among patients and its careers in delivering Palliative Care.